Realizing Multilayered Soft Tissue Model Using Multithreading in Python - K, Jayasudha; G.Kabadi, Mohan. (International Journal of Engineering and Technology, 2018)
Interactive Virtual Reality based surgical simulators are gaining popularity where an inexperienced surgeon can practice the surgery irrespective of time and cost which is an effective way in medical training. In order to guarantee the real time performance, a multi-threading technique is applied to the model in different languages. This results in increased utilization of the processor resources and high update rate is achieved with a realistic rendering of the proposed graphics model for the virtual reality simulation. This paper presents a comparative analysis of the model’s performance using multithreading process. This is based on addition of matrices of the 3D model simulation with large dimensions in C and python programming languages implementations.